(3TQM GdQSGdI GdeGQOjfjIs - (3eLghds; (3GdeGQOjfjs
(3ChdgG (B:s
(3CMeO jG ef CWdY YHGOg Ydi Ch bGJ GdYHGOI hHYO adeG cGf GdQHY GdeLjH CfaY GdBdGJ GdJi jJhSd HgG Zdi eYQaI SeJ GdbHdI hGdChbGJ hcGfJ ef QSGFdI GdebHhdI s
(3BNQgG (B:s
(3Ydi bOQ Jdc GdbhS GdeaQhVI ef Chd bhS GdEQJaGY ceG SHb Ke JVY GdeQF Ydi JbGWY GdNjW dCeYgG Ci eY Jdc GdbhS GdKGfjI ajchf GdeQi Ydi bOQ LjH Pdc GdJeGe GdMeO ddg Ydi GdENJJGe JeJ GdQSGdI GdeSei HGdQHY GdeLjH s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3eUOQ GbJfGA GdCUd (B:s
(3djOf s
Keywords: (3Gdadcs